Simplicity in Legislative Drafting and Rewriting Tax Legislation - Richardson, Ivor (Victoria University of Wellington Law Review, 2012)
The search for simplicity in legislative drafting affects all legislatures. It is also central to the work of the New Zealand Law Commission and of governments in other comparable jurisdictions. Rather than exploring a range of statutes in various jurisdictions, this article focuses on income tax. It does so for two reasons. The first is that income tax has been crucial to the funding of government in common law jurisdictions and to achieving a legislative balance between simplicity and other criteria of an acceptable tax system. The second is that we can draw on three recent projects to rewrite income tax legislation – in Australia, the United Kingdom and New Zealand.